Conservative management of congenital hepatic hemangioma complicated by ascites. Issue 7 (14th July 2022) - Hoornaert, Emmy; Clapuyt, Philippe; Dumitriu, Dana; Niel, Olivier; Huybrechts, Sophie; Scheers, Isabelle; Sokal, Etienne; Reding, Raymond; Stephenne, Xavier
Abstract: Involution of a rapidly involuting congenital hemangioma is an unknown cause of neonatal ascites. As involution phase is completed by 14 months after birth, conservative management with diuretics and drainage is possible and may avoid surgical resection. Abstract : Consider conservative management of congenital hepatic hemangioma complicated by ascites before embarking on a major surgery.